Political stability, investement and economic growth:Empirical study on Africa - (:unkn) unknown (My University, 2022)
Political stability has a very significant role in the economic development process of a country. The study of the effect of politicalstability on economic growth is one of the structural priorities whether it be at the academic, political or societal level. The interest of this work is to determine the impact of political stability on economic growth using the system-GMM estimator for dynamic panel data models on a sample of 48 African countries, for a 20-year period between 2000 and 2020. The main results of this paper are that political stability is a key variable determining growth, that the effect of political stability on growth isstatistically significant, and that investment in a politically stable environment has a positive impact on growth.Keywords: Africa, political stability, economic growth, political stability index, Hausman test, panel data econometrics.
Keywords: African Research